Psychological and Social Health of Physical Activity In Menopause Women - Hayati, Sri; Sansuwito, Tukimin Bin (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Introduction:. o chart peer-reviewed literature regarding the psychological and social health outcomes of physical activity (PA) around menopause in a systematic manner. Materials and Methods: The method used was a literature review where data was obtained from an electronic database, namely Google Scholar, Pubmet, Scopus between 2018-2024 have 68 after check the articles were found, 7 articles were selected that were in accordance with the objectives of this research. Manual checking of reference lists was also performed. The selection process was guided by the stages in PRISMA-ScR. Results: For all studies, surveys were the primary method of measuring psychological and social health outcomes, in cross-sectional studies (3 papers), intervention studies (3), longitudinal cohort studies (1) and one paper reporting a mixed-method study. The dataset comprised a total of women, with an average age of 52.6 and a variety of menopausal states. Most of the studies involved primarily Caucasian, relatively healthy, married and employed participants. Nineteen psychological and social health outcomes were assessed, including psychological menopause symptoms (N = 34), quality of life (N = 33), satisfaction with life (N = 7) and self esteem (N = 5). Conclusion: Collectively, the findings of these studies indicate a relatively evident positive impact of PA on the respective health outcomes, with only a few studies reporting no association. It is also noteworthy that most studies did not report any difference related to menopausal status. Future studies would benefit from, inter alia, a qualitative approach to lived experiences of psychological and social health outcomes of PA during the menopausal transition.